SELF-ASSESSMENT (WITH GUIDANCE) PRACTICES OF A THESIS PROPOSAL BY POSTGRADUATE STUDENTS IN A STATE UNIVERSITY IN WEST JAVA INDONESIA - Ai Fatmawati, - (2023)
This study aims to investigate postgraduate students' self-assessment (with guidance) practice in writing thesis proposals, including the benefits and problems students encounter. The research design of this study was a qualitative approach with a case study involving four postgraduate students in a state university in Bandung, who had examined their thesis proposal and had supervision meetings with their academic supervisor. The data were collected through document analysis and interviews. It was then analyzed through content and thematic analysis to identify the findings. The significant findings in this study are related to postgraduate students' understanding of self-assessment in writing, articulating expectations of thesis proposal, self-assessing thesis proposal, and the benefits and challenges in doing self-assessment with guidance. The results show that students understand and have been familiar with the practice of self-assessment in writing. They learned the thesis proposal structure from one of the lectures. With the assistance of the academic supervisor's feedback, students self-assess and revise their drafts. They found self-assessment with feedback beneficial in improving their writing quality, raising awareness of their limitation, and learning responsibility. However, they also discovered challenges, such as needed for more expertise in developing thesis proposals and students' external problems. The findings of this study revealed that the result of self-assessment by the students is more accurate when they are directed by their supervisor. Students cannot solely assess their writing. Therefore, further research on the applicability of self-assessment concept by students should be conducted.